Relationship between selected biopsychosocial factors on cognitive functions among Malaysian community-dwelling older adults - Foong, Hui Foh (2018)
Preservation of cognitive function is crucial to healthy ageing. Metabolic syndrome and depression are established risk factors for poor cognitive function in older adults. Nevertheless, there has been limited study exploring the mechanism underlying the relationship between metabolic syndrome and cognitive function as well as the variable that can moderate the negative effects of depression on cognitive function. Thus, the objectives of this study were to examine if chronic medical condition mediates the relationship between metabolic syndrome and cognitive function, and to investigate if intrinsic religiosity moderates the association between depression and cognitive function. The data were obtained from a national study in Malaysia entitled “Longitudinal Study on Neuroprotective Model for Healthy Longevity.” The original purpose of this study was to prospectively examine the degree of cognitive decline and its associated risk factors. However, only baseline data from the first wave of data collection were used in this study. Data analyses were carried out after examining the data for coding error, identifying and removing outliers, replacing missing values, and addressing normality issue. The main statistical analyses involved in the current study were Pearson’s correlation, chi-square test, multiple linear regression, and structural equation modelling. Results showed that age, year of education, household income, systolic blood pressure, body mass index, number of chronic medical condition, depression, intrinsic religiosity, gender, marital status, ethnicity, and living arrangement were significantly associated with cognitive function. Predictors of poorer cognitive function were being women, being older, being divorced or separated, lower year of education, lower household income, higher fasting blood sugar, higher cholesterol ratio, higher depressive symptoms, and lower intrinsic religiosity. Furthermore, chronic medical condition partially mediated the association between metabolic syndrome and cognitive function as well as intrinsic religiosity moderated the relationship between depression and cognitive function. The findings of the study implied that metabolic syndrome might increase the likelihood of older adults to suffer more chronic medical conditions and consequently, these responses might reduce their cognitive function. Besides that, intrinsic religiosity might reduce the negative effects of depression on cognitive function. To promote good cognitive function, specific intervention to minimise the number of chronic medical conditions by reducing the vascular risk factors is warranted. Moreover, professionals who are working with depressed older adults should seek ways to improve their intrinsic religiosity as one of the strategies to promote good cognitive function.